Evaluation of Clinical and Radiological Factors Determining the Need of Post-operative Ventilator Requirement in Patients of Esophageal Atresia - Ajay Kumar Verma; Anand Pandey; Gurmeet Singh; Ashish Wakhlu; Archika Gupta; Jiledar Rawat; Shiv Narain Kureel (EL-Med-Pub, 2018)
Objective: Ventilator requirement is an important constituent of post-operative care of patients of esophageal atresia (EA). In contrast to the developed world, the situation is very different in developing countries where the resources are limited, and ventilator may not be available to all patients of EA. This study was conducted to assess whether there are certain criteria, which may predict the possibility of non- requirement of ventilator for patients of EA in the post-operative period. Design: This study was a retrospective observational study. Setting: This study was conducted at a tertiary care teaching hospital. Duration: This study was conducted from 5 years and 6 months. Materials and Methods: We used certain parameters to assess the requirement of ventilators for the patients in the post-operative period. These included the presentation of patients before or after 3 days of life and birth weight (BW) of more or <2.5 kg. Presence of respiratory distress (RD) was analyzed. The presence of consolidation on X-ray was also evaluated. Results: The total number of patients was 175. In univariate analysis, the need of ventilator was significantly higher in patients presenting after 3 days of life, weight <2.5 kg, presence of RD, and pneumatic patch. In multivariate analysis, the age of presentation, weight, RD, and consolidation were found to independent factor for the ventilator requirement. Conclusion: On the basis of clinical and radiological features, namely, age, sex, BW, RD, and consolidation, we may prioritize these patients of EA, who may not be requiring the ventilator in the post-operative period. Further prospective studies on the basis of these factors may substantiate our efforts.